A Gambaran Pola Penggunaan Obat Antipsikotik Kombinasi Pada Pasien Skizofrenia Paranoid Rawat Jalan di Rumah Sakit Jiwa Dr. Soeharto Heerdjan : Gambaran Pola Penggunaan Obat Antipsikotik Kombinasi Pada Pasien Skizofrenia Paranoid Rawat Jalan di Rumah Sakit Jiwa Dr. Soeharto Heerdjan - Hutagaol, Sartika; Veriyanti , Putu Rika; Jerry, Jerry; Wulandari, Ainun; Putri , Elvina Triana; Febriani, Amelia; Winahayu, Neng Esti (Ruang Ide Publisher, 2023)
Overview Of The Pattern Of Use Of Combination Antipsychotics Drugs In Outpatient Paranoid Schizophrenia At Dr. Soeharto Heerdjan Hospital Abstract Schizophrenia is a severe mental disorder characterized by impaired reality values in the form of hallucinations and delusions. This study aims to determine the pattern of use of combination antipsychotic drugs in outpatients with paranoid schizophrenia at Dr. Mental Hospital. Suharto Heerdjan. This study is descriptive and data collection is retrospective and the sample data obtained are 109 patients. The results showed that the most paranoid schizophrenic patients in the 35-44 year age group were 51 patients (46.79%), 80 patients (73.40%) were male, 42 patients (38.53%) had high school education, not working as many as 89 patients (81.65%), unmarried as many as 88 patients (80.73%), long suffering 1-5 years as many as 57 patients (52.30%), without complaints, calm and cooperative as many as 94 patients (86.24%). The most widely used group of drugs was atypical – atypical combination antipsychotic drugs as many as 66 patients (51.36%). The most widely used therapy was the combination of risperidone + clozapine (54.54%). The use of antipsychotic drugs in outpatient paranoid schizophrenia patients at the Dr. Soeharto Heerdjan Hospital had the right indication, the right drug, the rightdose and frequency of the drug, the right route of administration, the right time administration and alert for side effects. Keywords: Antipsychotics; paranoid schizophrenia; drug use pattern